Sound radiation from non-uniformly lined duct with partial rigidity - TİRYAKİOĞLU, BURHAN (My University, 2021)
Radiation of sound waves by a semi-infinite circular cylindrical pipe with non-uniform lining is analyzed by using the Jones\" method in conjunction with the mode matching technique. This mixed method of formulation gives rise to a scalar Wiener-Hopf equation. The inner surface of the duct is coated by acoustically absorbing different linings. In the present study, different linings with partial rigidity make the problem more interesting when it is compared with the uniform lining. The solution of the considered problem involves three infinite sets of coefficients satisfying three infinite systems of linear algebraic equations. Numerical solutions of these systems are obtained for various values of the parameters of the problem and their effects on the radiation phenomenon are shown graphically. The solution is compared graphically with a similar study existing in the literature. A perfect agreement is observed between the both results.
Keywords: Matematik; Bilgisayar Bilimleri; Fizik; Genel Fizik; Temel Bilimler; Mathematics; Computer Science; Physics; General Physics; Natural Sciences; MATEMATİK, UYGULAMALI; Temel Bilimler (SCI); FİZİK, MATEMATİK; MATHEMATICS, APPLIED; MATHEMATICS; Natural Sciences (SCI); PHYSICS, MATHEMATICAL; PHYSICS; Analysis; Applied Mathematics; Algebra and Number Theory; Numerical Analysis; Mathematics (miscellaneous); Modeling and Simulation; General Mathematics; Computational Theory and Mathematics; Mathematical Physics; Physical Sciences; Wiener-Hopf technique; mode matching method; Fourier transform; saddle point technique; CYLINDRICAL DUCT; ACOUSTIC-WAVES; IMPEDANCE; SCATTERING; FLOW; PROPAGATION; DIFFRACTION; PIPE